Safety of repeated doses of tetanus toxoid, reduced diphtheria toxoid, and acellular pertussis vaccine in adults and adolescents. Issue 8 (3rd June 2018) - Jackson, Michael L.; Yu, Onchee; Nelson, Jennifer C.; Nordin, James D.; Tartof, Sara Y.; Klein, Nicola P.; Donahue, James G.; Irving, Stephanie A.; Glanz, Jason M.; McNeil, Michael M.; Jackson, Lisa A.
Abstract: In light of waning immunity to pertussis following receipt of tetanus toxoid, reduced diphtheria toxoid and acellular pertussis (Tdap) vaccine, maintaining protection may require repeated Tdap vaccination. We evaluated the safety of repeated doses of tetanus‐containing vaccine in 68 915 nonpregnant adolescents and adults in the Vaccine Safety Datalink population who had received an initial dose of Tdap. Compared with 7521 subjects who received a subsequent dose of tetanus toxoid, reduced diphtheria (Td) vaccine, the 61 394 subjects who received a subsequent dose of Tdap did not have significantly elevated risk of medical visits for seizure, cranial nerve disorders, limb swelling, pain in limb, cellulitis, paralytic syndromes, or encephalopathy/encephalitis/meningitis. These results suggest that repeated Tdap vaccination has acceptable safety relative to Tdap vaccination followed by Td vaccination.